Diversity, interculturalism and community building in the Algarve: Preliminary findings for (re)imagining a digital road map of hope - Sílvia Leiria Viegas (Cidades, Comunidades e Território)
The Algarve is the first Portuguese region with more immigrants per inhabitant, and the second with the highest rate of immigration, after Greater Lisbon. These immigrants bring with them different cultures, traditions, religious beliefs and customs, and face many barriers to local integration. Indeed the Algarve is a diverse reality with various forms of social discrimination and spatial segregation affecting many, including economic and forced migrants. The aim of the article is to identify the urban specificities of the region; the accounts of these immigrants about their living conditions, especially in terms of housing and employment, their support activities and cultural interactions; and the digital media that transmit and amplify perceptions of threat, but also make visible (self-)representations and opportunities. Another aim is to provide a political-philosophical lens for the production of a digital road map. Following Freire's and Harvey's ideas of hope, the reflections intersect with an exploratory empirical socio-spatial and digital recognition of Faro (and Estoi) and Loulé (and Quarteira). The article argues that intercultural dialogues, interactions and relationships based on local experiences and situated knowledge can help us imagine alternatives and more just worlds. Conclusions discuss the analytical guidelines of this digital road map (in terms of urban layers, migrant dots, digital fluxes) and the guidance it provides to support diversity, interculturalism and community building.